'I just felt sad and angry all in one thing': Jim Everett in conversation with Rebe Taylor on making the Nightingale. Issue 1 (2nd January 2020) - Taylor, Rebe; Everett, Jim
ABSTRACT: The symposium 'The Nightingale: Gender, Race and Troubled Histories on Screen' opened with a discussion between Jim Everett, the film's associate producer and Aboriginal consultant, and Associate Professor Rebe Taylor, Senior Research Fellow in the College of Arts, Law and Education at the University of Tasmania. Rebe and Jim have known each other since 1999, when they met at a history conference: as Rebe noted, 'we've never really stopped talking since then.' Jim is a Senior Indigenous scholar at the University of Tasmania and he is currently working on a Master's thesis with Rebe. In this (edited) transcript of their conversation, Rebe and Jim discuss the way he came to be involved with the film, the casting and production process, and his reaction to the finished film.